Duration of action of sodium cromoglycate on exercise induced asthma: comparison of 2 formulations. Issue 8 (August 1983) - Bar-Yishay, E; Gur, I; Levy, M; Volozni, D; Godfrey, S
Abstract : Thirteen asthmatic children aged 9-14 years participated in a double blind randomised trial to compare the effectiveness and duration of action of 2 formulations of sodium cromoglycate; one a 20 mg capsule of powdered sodium cromoglycate delivered by turbo inhaler (spinhaler), and the other 1 mg of aerosolised sodium cromoglycate delivered by pressurised cannister inhaler (aerosol). The children performed exercise tests on each of 3 days in a 10 day period--15 minutes, 2 hours, and 6 hours after inhalation of powder, aerosol, or a placebo. Two patients were not protected from exercise induced asthma by either formulation of sodium cromoglycate. Among the remaining patients both formulations gave good protection from exercise induced asthma 15 minutes after inhalation, and the effect of both wore off steadily over the next 6 hours. The spinhaler gave appreciably better protection than the aerosol at 15 minutes after inhalation, and was the only formulation to provide good protection at 2 hours and 6 hours. The more limited effectiveness of the aerosol may be explained by the lower dose of sodium cromoglycate and the more complicated inhalation technique required.